2008
DOI: 10.1186/1753-2000-2-19
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome and prognosis of dissociative disorder with onset in childhood or adolescence

Abstract: Background: In the majority of cases short-term treatment outcome of juvenile dissociative disorder is rather favourable. In contrast, the long-term course seems to be less positive, but meaningful results are still fragmentary. The aim of this follow-up study is to bridge this gap to some extent describing the long-term outcome of juvenile dissociative disorder in a clinical sample. To our knowledge there is no comparable other long-term follow-up study which is based on a case definition according to actual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“… 6 Diagnostic mistakes in the group of patients in the developmental age are estimated between 0-17%. 7 In the case of our patients with somatoform or somatoform and conversion disorders the period of time between the breakout of the disease and final diagnosis was significantly longer than for patients from the control group, which may indicate that their GPs had diagnostic problems - more than 30% of patients had to wait three or more years for their final diagnosis (Supplementary Table 4). It has to be emphasized that acceptance of diagnosis of somatoform and conversion disorders is sometimes difficult for the patients and their families.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“… 6 Diagnostic mistakes in the group of patients in the developmental age are estimated between 0-17%. 7 In the case of our patients with somatoform or somatoform and conversion disorders the period of time between the breakout of the disease and final diagnosis was significantly longer than for patients from the control group, which may indicate that their GPs had diagnostic problems - more than 30% of patients had to wait three or more years for their final diagnosis (Supplementary Table 4). It has to be emphasized that acceptance of diagnosis of somatoform and conversion disorders is sometimes difficult for the patients and their families.…”
Section: Discussionmentioning
confidence: 83%
“…9 Therapy and problem solving should start before reaching maturity as conversion disorders have better prognosis in children and adolescents. 7 , 10…”
Section: Discussionmentioning
confidence: 99%
“…If this pattern of quicker response to treatment is found with youth, early identification and treatment of DD will be critical. In particular, long-term follow-up studies with children are needed because some research indicates that the initial positive response to treatment observed in children and adolescents, particularly among those diagnosed with conversion disorder rather than complex DD such as DID and DDNOS, may not endure for many patients (Jans et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…1993). PN'nin diğer belirtilere oranla en sık görülen KB tipi olduğu belirtilmektedir (Jans ve ark. 2008, Martinez-Toboas ve ark.…”
Section: Introductionunclassified